Weakening the Solvating Power of Solvents to Encapsulate Lithium Polysulfides Enables Long‐Cycling Lithium–Sulfur Batteries - Hou, Li‐Peng; Li, Zheng; Yao, Nan; Bi, Chen‐Xi; Li, Bo‐Quan; Chen, Xiang; Zhang, Xue‐Qiang; Zhang, Qiang (Advanced materials (Weinheim), 2022)
Long cycling lifespan is a prerequisite for practical lithium–sulfur batteries yet is restricted by side reactions between soluble polysulfides and the lithium‐metal anode. The regulation on solvation structure of polysulfides renders encapsulating polysulfides electrolytes (EPSE) as a promising solution to suppress the parasitic reactions. The solvating power of the solvents in the outer solvent shell of lithium polysulfides is critical for the encapsulation effect of EPSE. Herein, 1,1,2,2‐tetrafluoroethyl‐2,2,3,3‐tetrafluoropropyl ether (HFE) is demonstrated as a superior outer‐shell solvent to construct EPSE. Based on the large steric hindrance of the fluorohydrocarbon chains, the electron‐withdrawing perfluoro segment (CF2 further endows HFE with prominently weak solvating power. The HFE‐EPSE improves the lifespan from 54 to 135 cycles for lithium–sulfur batteries with an ultrathin lithium‐metal anode (50 µm) and high‐areal‐loading sulfur cathode (4.4 mg cm−2). Furthermore, a 334 Wh kg−1 lithium–sulfur pouch cell (2.4 Ah level) with HFE‐EPSE stably undergoes 25 cycles. This work demonstrates the role of weakening solvating power of outer‐shell solvents to construct superior EPSE and inspires the significance of the solvation chemistry of polysulfides to achieve practical lithium–sulfur batteries. The large steric hindrance of its fluorohydrocarbon chains and the electron‐withdrawing CF2 segments endow 1,1,2,2‐tetrafluoroethyl‐2,2,3,3‐tetrafluoropropyl ether with prominently weak solvating power and high reduction stability. The weakening solvating power of fluorohydrocarbon solvent leads the formation of encapsulating‐lithium polysulfide electrolyte for lithium–sulfur pouch cells with long cycling lifespan.